A randomized comparative evaluation of clinical and home application to investigate the effectiveness of silver nitrate (AgNO3) (95%) for the treatment of verruca pedis. (17th February 2017) - Concannon, Michael; Keogh, Lisa; Stephenson, John; Parfitt, Grace; Forrest, James
Abstract: Objective: To investigate the clinical effectiveness of silver nitrate (95%) for the treatment of verruca pedis comparing professional and self-application treatments. Methods: A single-centre, two-armed randomized evaluation was conducted at a University podiatry clinic. A total of 113 participants (101 analysed) with verruca pedis were included. Participants were randomized to either a clinical group, where silver nitrate was applied by a healthcare professional or a home group, where silver nitrate was self-applied. The main outcome measure was post-treatment pain, controlling for pre-treatment pain, and resolution of the verruca. Secondary outcome measures were participant satisfaction, partial reduction in the verruca and ease of use of the product. Key findings: The study showed no significant difference between home treatment and clinically applied treatment for the treatment of verruca pedis in either primary outcome; however, a substantive difference in resolution between groups was recorded, with 34.0% full resolution and 26.4% partial resolution in the clinical treatment group, and 18.8% full resolution and 37.5% partial resolution in the home treatment group. Participants widely reported general ease of use of the product. All participants reported a reduction in pain as a result of the intervention. Conclusion: Silver nitrate has been shown to be a safe and effective treatment for verruca pedis, with equal success rates when compared between home and clinical applications.